Sulfate-chloride sodium-magnesium mineral waters modulate neuroendocrine-immune complex and metabolism in healthy female rats - Popovych, Daria; Badiuk, Nataliya; Hrytsak, Myroslava; Ruzhylo, Sofiya; Mel’nyk, Oksana; Zukow, Xawery (Journal of Education, Health and Sport, 2021)
Background. Earlier in an experiment on rats, we showed that newly created sulfate-chloride sodium-magnesium drinking mineral waters of Truskavets’ spa has a significant modulating effect on the parameters of metabolism and the autonomic nervous, endocrine and immune systems. In this study, we combined data obtained on the same animals, in line with the concepts of neuroendocrine-immune complex and functional-metabolic continuum. Materials and Methods. Experiment was performed on 50 healthy female Wistar rats 230-290 g divided into 4 groups. Animals of the first group remained intact, using tap water from drinking ad libitum. Rats of the second (control) group for 6 days administered a single tap water through the tube at a dose of 1,5 mL/100 g of body mass. The rats of the main groups received the water "Myroslava" and "Khrystyna". The object of the study were the metabolic, neuro-endocrine and immune parameters. Results. The method of discriminant analysis revealed 31 parameters, according to which all four groups of animals differ from each other. Classification accuracy is 100%. Conclusion. The newly created sulfate-chloride sodium-magnesium drinking mineral waters of Truskavets’ spa has both similar and specific effects on the neuroendocrine-immune complex and metabolism at healthy old female rats with weekly use. This provides a basis for preclinical studies.